Komunikasi Keluarga Sebagai Pelindung Versus Pengaruh Peer GROUP Sebagai Risiko pada Perilaku Seksual Remaja - Lisma Eva Reny; Nadia Resya Inggrida (Jurnal Bidan Mandiri, 2026)
Adolescent premarital sexual behavior is a persistent reproductive health issue with negative psychological and physiological impacts. This study aimed to determine the relationship between the quality of adolescent communication with parents and the influence of the peer group on Adolescent premarital sexual behavior among students at SMAN 4 Bukittinggi. This quantitative study employed a Cross-Sectional design. The sample consisted of 68 students selected using proportional random sampling. Data were collected via questionnaires and analyzed using the Chi-Square test. The results showed that there was a significant relationship between parental communication and PSPB (p=0.01; RP=4.781), and a significant relationship between peer group and PSPB (p<0.05; RP=2.22). Adolescents with less quality communication with their parents were 4.781 times more likely to engage in PSPB, and 53.1% of those with poor communication were at high risk. It is concluded that quality communication with parents and positive peer group influence are vital protective factors. The school environment must be strengthened to improve effective communication education and reproductive health promotion.